Recognition by recombinant autoimmune thyroid disease-derived Fab fragments of a dominant conformational epitope on human thyroid peroxidase. - Portolano, S (1992)
To characterize the nature of thyroid peroxidase (TPO) autoantibodies present in the sera of patients with autoimmune thyroid disease, we cloned three IgG1/kappa Fab fragments which bind 125I-TPO. This was accomplished by the molecular cloning and expression in bacteria of IgG gene fragments from B cells infiltrating the thyroid of a patient with Graves' disease. The three Fab fragments (SP2, SP4, and SP5) are coded for by a common heavy chain (VH1, D, JH3) and three related, but different, light chains (VK1, JK2). The SP Fab fragments bind specifically to TPO with high affinities (6 x 10(-11)-2 x 10(-10) M) comparable to those of serum TPO autoantibodies. TPO autoantibodies represented by the SP Fab fragments are present in all 11 patients studied, constitute a high proportion (36-72%) of serum TPO autoantibodies in individual patients and interact with a conformational epitope on TPO.